1987
DOI: 10.1111/j.1476-5381.1987.tb11313.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium entry blockers on calcium‐dependent contractions of rat portal vein

Abstract: 1 The effects of six calcium entry blockers belonging to the dihydropyridine (isradipine or PN 200-110, nifedipine, nicardipine), verapamil (D888 or desmethoxyverapamil, D600 or gallopamil) and diltiazem classes were investigated on isometric spontaneous contractions and contractions induced by high-K+ solutions, noradrenaline, acetylcholine and caffeine. 2 The rank order of potency was PN 200-110>nicardipine=nifedipine=D888>D600>diltiaz-em from experiments on spontaneous contractions and high-K+ induced cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 20 publications
(31 reference statements)
6
28
0
Order By: Relevance
“…Using membranes of portal vein smooth muscle, we demonstrated that the (+)_[3H]-PN binding was of high affinity, saturable and reversible, and correlated well with the pharmacological activities determined from inhibition of the mechanical and electrical responses (Dacquet et al, 1987;. In portal vein smooth muscle strips, the affinity of (Kokubun et al, 1986) and vascular myocytes (Morel & Godfraind, 1987;Sumimoto et al, 1988 significantly icreased.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using membranes of portal vein smooth muscle, we demonstrated that the (+)_[3H]-PN binding was of high affinity, saturable and reversible, and correlated well with the pharmacological activities determined from inhibition of the mechanical and electrical responses (Dacquet et al, 1987;. In portal vein smooth muscle strips, the affinity of (Kokubun et al, 1986) and vascular myocytes (Morel & Godfraind, 1987;Sumimoto et al, 1988 significantly icreased.…”
Section: Discussionmentioning
confidence: 95%
“…state of the channel. (2) In contraction experiments, the voltage-dependence of calcium channel blockade is indicated by a shift to the left of the doseinhibition curves measured in physiological solution or in K+-rich depolarizing solution (Dacquet et al, 1987). (3) The third method is to use radioligand binding techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Contractions of portal vein longitudinal strips were measured with an isometric force transducer (Akers 801) as previously described (Dacquet et al, 1987 (Hamill et al, 1981). Whole-cell Cl-currents were recorded in response to 10-5M NA applied from a glass pipette with a pressure ejector.…”
Section: Contraction Measurementsmentioning
confidence: 99%
“…In portal vein smooth muscle, stimulation of a1-adrenoceptors produces contraction that involves release of Ca2+ from intracellular stores and Ca2 + influx through voltage-dependent Ca2 + channels (Mironneau & Gargouil, 1979;Dacquet et al, 1987). The NAinduced contraction is associated with a depolarization and an increase in membrane conductance (Takata, 1980;Nanjo, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of al-adrenoceptors in portal vein smooth muscle produces contraction that can be dependent on an increase in both calcium influx through voltage-dependent channels and release of calcium from intracellular stores (Mironneau & Gargouil, 1979;Dacquet et al, 1987;Pacaud et al, 1987). However, there are recent results concerning the ionic mechanisms underlying the electrophysiological early response to noradrenaline in veins which indicate that the noradrenaline-induced depolarization is mainly mediated by an increase in membrane chloride conductance (Byrne & Large, 1988a, b;Van Helden, 1988).…”
Section: Introductionmentioning
confidence: 99%